Teamwork self-efficacy and employee satisfaction: a sequential framework to build employee cohesion - Priya, A. Shakti; Christopher, B. Prabu (International Journal of Public Health Science (IJPHS), 2024)
The occupational psychological health of the employees is affected by the behavior of their peers in the workplace. To reduce psychological stress and improve the well-being of employees, organizations are focusing on developing coherence through various human resources practices. In the current business scenario, it is crucial to address psychological stress by building employee cohesion. The aim of this study is to analyze how employees’ teamwork self-efficacy influences group cohesion through employee satisfaction. This study followed a quantitative approach to test the data, which comprises 228 information technology (IT) professionals, working in top IT companies in India. This study used a partial least squares structural equation modeling approach to test the hypothesis. The results revealed that employees’ teamwork self-efficacy is not directly influencing employee cohesion, whereas it has a significant positive influence on an employee’s cohesion only with the mediation effect of an employee’s satisfaction. Predominantly, an employee’s extrinsic satisfaction has a greater influence on the aforesaid relationship than an employee’s intrinsic satisfaction. The results of this study suggest human resources development practitioners place more emphasis on delivering motivational benefits and providing collaboration-oriented interventions that strengthen teamwork self-efficacy, since these factors may directly affect employee cohesion given that a large portion of the respondents were young adults.